Knowledge Management Maturity Model of Higher Education Based-on Quality Culture and Human Resource Management Practices - Anik Herminingsih; Srilanggeng Ratnasari (Eduvest - Journal of Universal Studies, 2024)
There are 2 main important things to improve knowledge management maturity (KMM), namely organizational culture and proper HR management. There are no studies on human resource culture and management that are specific to increasing KMM in tertiary institutions. Empirical research on the influence of higher education quality culture as a goal of implementing the Internal Quality Assurance System (SPMI) on all tertiary institutions in Indonesia and the influence of HR management on KMM is still very limited. This study aims to develop a model for improving KMM in Indonesian universities through the implementation of a quality culture and human resource management. The analysis was carried out with a structural equation model (SEM). The results showed that quality culture had a positive and significant effect on human resource management practices, but had no direct effect on knowledge management maturity. Human resource management practices have a positive and significant effect on knowledge management maturity. The results of this study prove the importance of the quality culture of higher education in developing mature knowledge management, through human resource management practices.